From the first equation, \( y = 2x - 8 \). Substitute this expression for \( y \) into the second equation: \[ 3x + 2(2x - 8) = -2 \]
Expand and simplify the equation: \[ 3x + 4x - 16 = -2 \] \[ 7x - 16 = -2 \]
Add 16 to both sides of the equation: \[ 7x = 14 \] Divide both sides by 7: \[ x = 2 \]
Substitute \( x = 2 \) back into the first equation to find \( y \): \[ y = 2(2) - 8 \] \[ y = 4 - 8 \] \[ y = -4 \]
\[ x = \boxed{2} \] \[ y = \boxed{-4} \]
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.